Vancomycin use, dosing and serum trough concentrations in the pediatric population: a retrospective institutional review. - Rajon K; Vaillancourt R; Varughese N; Villarreal G (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Vancomycin is used primarily for Gram-positive infections. Recommended dosage regimens and targeted therapeutic levels vary between institutions. Objectives: This study aims to describe therapeutic levels according to initial vancomycin doses and patient's age. A secondary objective was to evaluate appropriateness of vancomycin use in our hospital. Methods: A retrospective chart review was conducted at the Children's Hospital of Eastern Ontario. Patients included in this study were classified by age (neonates, infants, children and adolescents) and categorized into those who received vancomycin ≤5 and >5 days. Initial vancomycin dosing regimens and corresponding initial trough levels obtained were evaluated. Initial trough levels drawn in relation to the third, fourth, or fifth doses corresponding to the first course of therapy were analyzed. Acceptable trough levels ranged from 5-20 mg/L. Results: One-hundred-and-sixty-four patients who received intravenous vancomycin in 2013 were included. Of the 229 courses of vancomycin, 190 (83%) were used 5 days or less (mean 4.9 days). Sixteen infants (88.9%) and 21 adolescents (100%), who received vancomycin empiric dosing of 60 mg/kg/day, had initial trough levels >5mg/L. However, in the children's group 20 (37.7%) did not reach levels >5 mg/L. None of vancomycin minimum inhibitory concentration (MIC) values were >1mg/L for the four patients who had infections due to methicillin-resistant Staphylococcus aureus strains. Conclusions: In our institution, initial empiric vancomycin dosing of 60 mg/kg/day resulted in levels ≥5mg/L in most infants and adolescents. It remains unclear why some children aged 1-12 years did not achieve these levels.